The superb programme vol.2 - Jarman, Derek (Roma : Raro Video, 2004)
Contains: In the Shadow of the Sun (1974), The Art of Mirrors (1973), Ashden's Walk on Mon (1973), Stolen Apples for Karen Blixen (1973), Journey to Avebury (1971)
Onderzoek KASK Professioneel (OFVP)
film
Keywords: Jarman, Derek